EFEKTIVITAS PELAKSANAAN PROGRAM KAMPUNG KELUARGA BERENCANA (KB) KOTA PEKANBARU - Anggraini, Tiara; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Kampung KB Program is a Government Program in the framework of contorlling population and familly planning in order to succeed the development priority agenda (Nawacita) in point number three